Hubungan kecerdasan emosional dengan keterampilan berpikir kritis pada pembelajaran IPAS peserta didik kelas VI sekolah dasar Se-Gugus 1 Kecamatan Serengan - Putri Maulidya Febri; Matsuri Matsuri (Universitas Sebelas Maret, 2025)
Critical thinking skills include skills that individuals use to analyze and evaluate information in depth to find the right solution. Emotional intelligence can help students develop critical thinking skills. Emotional intelligence helps students understand and manage emotions, empathize, self-motivate, and be able to solve problems. This study aims to determine the relationship between emotional intelligence and critical thinking skills in science learning for grade VI elementary school students in Cluster 1, Serengan District. This study uses a quantitative approach with a correlational method. This research was conducted at SDN Bunderan No. 164, SDN Danukusuman, and SDN Slembaran with total of 68 students. The results of this study explain that students have a level of emotional intelligence and critical thinking skills in the moderate category. The results of the hypothesis test using the Pearson Product Moment method showed a significance value (Sig. 2-tailed) <0.001 with a Pearson correlation value of 0.597. It can be concluded that there is a positive and significant relationship between emotional intelligence and critical thinking skills in the moderate category. Emotional intelligence has a role in forming critical thinking skills but is not a dominant factor, so there are other factors that contribute to critical thinking skills.